Early identification of stroke symptoms and risk factors using the BE FAST method: benefits of early intervention in high-risk populations - Zang, Jiejin; Bai, Qiulian; Xiong, Xianmei; He, Ping; Sun, Jing; Gong, Xiaowei (Frontiers in Neurology, 2025)
BackgroundTimely recognition of stroke symptoms is essential for optimizing treatment and improving outcomes. The BE FAST (Balance, Eyes, Face, Arms, Speech, Time) mnemonic is a practical tool designed to enhance early identification of stroke in community and clinical settings. This study aimed to evaluate the clinical impact of implementing the BE FAST method in high-risk populations presenting with suspected acute stroke.MethodThis retrospective cohort study included 433 patients who presented with acute stroke symptoms between January 2020 and December 2023. Patients were divided into two groups: those assessed using the BE FAST method (n = 212) and those evaluated through standard clinical observation or patient/family reporting (n = 221). Key outcomes included time from symptom onset to hospital arrival, rate of thrombolysis or thrombectomy, neurological improvement based on NIHSS scores, length of hospital stay, and in-hospital mortality. Multivariate logistic regression was used to adjust for potential confounders.ResultsPatients in the BE FAST group had significantly shorter median time from symptom onset to hospital arrival (82 min vs. 141 min, p < 0.001), and higher rates of intravenous thrombolysis (35.8% vs. 23.1%, p = 0.004). Neurological improvement (NIHSS score improvement ≥4 at discharge) was observed in 61.3% of BE FAST group patients versus 39.8% in the control group (p < 0.001). The BE FAST group also had a lower in-hospital mortality rate (3.8% vs. 7.7%, p = 0.047) and shorter average hospital stays (6.2 ± 2.5 days vs. 8.1 ± 3.0 days, p < 0.001). BE FAST use remained an independent predictor of favorable neurological outcomes after adjustment for age, sex, comorbidities, and initial stroke severity.ConclusionThe use of the BE FAST method significantly improves early stroke recognition, facilitates timely intervention, and is associated with better clinical outcomes in high-risk populations. Widespread implementation of this tool in both pre-hospital and clinical settings may enhance stroke care pathways and reduce disability and mortality.